Are Peer Interventions for HIV Efficacious? A Systematic Review - Simoni, Jane M. (2011)
Behavioral interventions to prevent HIV or assist HIV-positive persons often incorporate peers, yet empirical support for their efficacy is only recently accumulating. We describe the results of a review of the global literature, identifying 117 studies evaluating the efficacy of peer-based interventions in the area of HIV/AIDS. About half were conducted in the developing world and half in Western nations. Across a range of populations and intervention modalities, the majority of studies provided some support for peer interventions according to outcome indicators in the domains of sexual risk behavior, attitudes and cognitions, HIV knowledge, and substance use. However, outcomes assessed using biomarkers and other non-self-report variables were less likely to indicate intervention efficacy. Overall, findings suggest that we can have some confidence in peer interventions, yet more data are needed demonstrating an effect in the most rigorous study designs and with outcomes that are not potentially affected by respondent bias.